Estimasi Sumber Daya Ikan Cakalang (Katsuwonuspelamis) Dengan Metode Fox Berdasarkan Hasil Tangkapan Purse Seine Di Pelabuhan Perikanan Pantai Ogotua Kabupaten Toli-Toli - Anai, Sunnerta; Masyahoro, Masyahoro; Sulistiawati, Dwi (Mitra Sains, 2023)
Fisheries Management Area (FMA) 716 Sulawesi Sea and FMA 713 Makassar Strait are known as fishing ground for economically important fish. The research purpose for skipjack tuna (K. pelamis 1758) resources in a sustainable manner in the Maximum Sustainable Yield (MSY) management regime dimensions, usingsurvey method through observation, measurement and direct interviews at Ogotua Beach Fishing Port. The results of the analysis for the Fox model with MSY, Eopt and TAC values of 650.16 tons, 3370 trips and 520.13 tons respectively.